Malay Business Leaders’ Characteristics and Their Success in Business (Journal of Governance and Development (JGD), 2014)
This research is mainly focusing on the profile of successful Malay business leader in Malaysia. The major objectives were to study their characteristic that contributed to the successful in the business. The data for this research were collected from two sources, namely primary sources and secondary sources. The qualitative in-depth interview research technique was used for the primary data. A total of ten (10) successful Malay business leaders around Kedah and Perlis state were selected as respondents of this research. As for secondary data, five (5) successful Malay business leaders were analyzed based on the existing books and other sources documented their success. Based on the analysis, these leaders exhibit a vision in their life, intelligence, inspiring and compassionate. Besides, they are also very decisive, hardworking and committed in their work. These characteristic have proven to be key ingredients in their success and these traits are also present among successful business leaders of other ethnic groups.